A Survey of Knowledge, Attitudes, and Practices in Relation to Mosquitoes and Mosquito-Borne Disease in Western Australia - Potter, Abbey; Jardine, Andrew; Neville, Peter J. (Frontiers in Public Health, 2016)
On average, more than 1,000 individuals will acquire a mosquito-borne disease in Western Australia (WA) each year. Knowledge, attitudes, and practices (KAP) in relation to mosquitoes and mosquito-borne disease have not yet been investigated within Australia. A randomized telephone survey of 2,500 households across 12 regions in WA was undertaken between February and May 2014. The aim of the survey was to obtain baseline KAP data surrounding mosquitoes and mosquito-borne diseases in different regions of WA, across a range of age groups and between males and females. The results of this survey indicate that the majority of respondents are aware of the potential for mosquitoes in WA to transmit Ross River virus, while awareness of other endemic mosquito-borne diseases remains limited. Common misconceptions exist in relation to exotic mosquito-borne diseases, with respondents incorrectly identifying malaria and dengue as endemic diseases in WA. The survey also highlighted a range of important issues, such as limited awareness of the potential for backyard breeding in domestic containers, occupational exposure to mosquitoes in regions with a large employment base in the mining and resources sector, increased exposure to mosquitoes as a result of participation in outdoor recreational activities in the north of the State, and reduced awareness of mosquito-borne disease in individuals aged 18–34 years. The results of this study will be used to inform the development of a new communication strategy by the Department of Health, to further raise awareness of mosquito-borne disease in WA. The data will then provide a baseline against which to compare future survey results, facilitating the rigorous evaluation of new communication efforts.